Dermatophyte Resistance to Antifungal Drugs: Mechanisms and Prospectus - Martinez-Rossi, Nilce M.; Bitencourt, Tamires A.; Peres, Nalu T. A.; Lang, Elza A. S.; Gomes, Eriston V.; Quaresemin, Natalia R.; Martins, Maíra P.; Lopes, Lucia; Rossi, Antonio (Frontiers in Microbiology, 2018)
ABSTRACT Dermatophytes comprise pathogenic fungi that have a high affinity for the keratinized structures present in nails, skin, and hair, causing superficial infections known as dermatophytosis. A reasonable number of antifungal drugs currently exist on the pharmaceutical market to control mycoses; however, their cellular targets are restricted, and fungi may exhibit tolerance or resistance to these agents. For example, the stress caused by antifungal and cytotoxic drugs in sub-inhibitory concentrations promotes compensatory stress responses, with the over-expression of genes involved in cellular detoxification, drug efflux, and signaling pathways being among the various mechanisms that may contribute to drug tolerance. In addition, the ATP-binding cassette transporters in dermatophytes that are responsible for cellular efflux can act synergistically, allowing one to compensate for the absence of the other, revealing the complexity of drug tolerance phenomena. Moreover, mutations in genes coding for target enzymes could lead to substitutions in amino acids involved in the binding of antifungal agents, hindering their performance and leading to treatment failure. The relevance of each one of these mechanisms of resistance to fungal survival is hard to define, mainly because they can act simultaneously in the cell. However, an understanding of the molecular mechanisms involved in the resistance/tolerance processes, the identification of new antifungal targets, as well as the prospective of new antifungal compounds among natural or synthetic products, are expected to bring advances and new insights that facilitate the improvement or development of novel strategies for antifungal therapy.